Back Cover: Lipopeptide Nanoparticles: Development of Vaccines against Hookworm Parasite (ChemMedChem 10/2015). Issue 10 (October 2015) - Fuaad, Abdullah A. H. Ahmad; Pearson, Mark S.; Pickering, Darren A.; Becker, Luke; Zhao, Guangzu; Loukas, Alex C.; Skwarczynski, Mariusz; Toth, Istvan
<x xml:space="preserve">Abstract</x> The back cover picture shows the action of a vaccine candidate against hookworm. B‐cell peptide epitopes derived from hookworm protease Na‐APR‐1 were incorporated into lipid core peptides (structure shown on the right). Proper epitope conformation (β‐sheet and not α‐helix) was found to be crucial for pathogen protein recognition by the antibodies produced. More details can be found in the Full Paper by Mariusz Skwarczynski et al. on page 1647 in Issue 10, 2015. (DOI: 10.1002/cmdc.201500227).